The neurophysiology of the intervention strategies of Awareness Training Program on emotion regulation - Gao, Junling; Leung, Hang Kin; Fan, Jicong; Wu, Bonnie Wai Yan; Sik, Hin Hung (Frontiers in Psychology, 2022)
Emotion regulation is essential for healthy living. Previous studies have found that mental training such as compassion meditation could help with emotion regulation. However, the underlying neural mechanism and possible intervention strategies of group-based Mahayana Buddhist intervention involved in emotion regulation are still unclear. This event-related potential (ERP) study investigated how compassion and wisdom meditations, two key components of the Awareness Training Program (ATP), may regulate emotion during different mental processing stages, namely attention deployment, cognitive change, and response modification. Eighty-five middle-aged working adults with moderate stress were voluntarily recruited for this study, using a 128-channel electroencephalogram system. After seven weeks of training, participants (ATP attendance, n = 42; waitlist control, n = 43) were instructed to view negative pictures while practicing compassion or wisdom meditation, with corresponding priming words. Another normal priming condition and a neutral picture condition were set as control conditions. ERP results in the ATP group showed that negative pictures induced greater prefrontal activity (N400 component) in both compassion and wisdom meditation conditions compared with the normal condition, while the control group showed little difference between the conditions. Significantly higher heart rate variability was found in the compassion but not wisdom meditation when compared with the neutral priming condition. Correspondent changes in behavioural data were also found. Converging evidence showed that compassion meditation training could modulate negative emotion processing in stages of attention deployment, cognitive change, and behavioural responses. The prefrontal lobe could play an important role in the process of emotion regulation by compassion meditation, possibly due to the emphasis of the ATP on contemplative practices.